A study of the 26Mg(12C, 12B)26Al charge-exchange reaction - Etchegoyen, A.; Sinclair, D.; Liu, S.; Etchegoyen, M. C.; Scott, D. K.; Hendrie, D. L. (North Holland Publishin Co., 1983)
Fil: Etchegoyen, A. Comisión Nacional de Energía Atómica; Argentina